What is moving where? Infants’ visual attention to dynamic objects may assist with processing of spatial relations - Choi, Jihye; Park, Youjeong (Frontiers in Psychology, 2024)
A central question in infant spatial cognition concerns how infants form abstract categories of spatial relations such as support (on) and containment (in). Prior work suggests two different possibilities regarding the role of attention to objects in infants’ formation of abstract categories of spatial relations: Attention to objects may compete with (and thus hamper) attention to the spatial relations between them, or assist with encoding of the spatial relation information. Using eye-tracking, we examined how infants’ visual attention to objects related to their successful formation of an abstract category of support relations (i.e., an object on another). Thirty-eight 8-month-old infants’ eye movements were recorded during a support categorization task, where infants were habituated to four dynamic events depicting support relations (e.g., resting a block on a box) and then presented with test events that depicted either a support or containment relation with objects that they had seen or not seen in the habituation phase. Based on their looking time to the familiar versus novel spatial relation in the test, infants were classified into two groups: categorizers, who formed an abstract category of a support relation, and non-categorizers, who did not do so. During their initial phase of learning (i.e., the first habituation trial), categorizers paid greater attention to the object moved by a hand (i.e., the dynamic object) in comparison to non-categorizers, whereas their attention to the static object or their gaze shifts between the two objects did not differ. In addition, when presented with novel objects in a novel spatial relation after habituation, only categorizers displayed asymmetric attention between the objects, attending to the dynamic object more than the static object. Gaze shifts and attention to the concave area (i.e., hole) of the container did not differ between categorizers and non-categorizers. These findings suggest that infants’ focused attention to an object in motion may play a key role in young infants’ spatial category learning, and support the idea that attention to objects can assist with encoding of the spatial relational information.